Unveiling the sensitivity and significance of the Ni oxidation state for alkaline hydrogen oxidation electrocatalysis - Qihao Li; Zixiao Shi; Colin R. Bundschu; Christopher J. Pollock; Andrés Molina Villarino; Mihail R. Krumov; Rui Zeng; David A. Muller; Héctor D. Abruña (Proceedings of the National Academy of Sciences, 2026)
The development of nonprecious-metal-based hydrogen oxidation reaction (HOR) electrocatalysts remains as the bottleneck for achieving high-performance, platinum group metal-free (PGM-free) alkaline/anion exchange membrane fuel cells. Numerous efforts have been dedicated toward enhancing the HOR activity of Ni catalysts due to the lack of alternative choices. However, mechanistic insights relating to electrocatalytic activity and degradation remain a matter of debate, and proposed models tend to lack conclusive experimental evidence. Here, we studied the state of Ni catalysts using scanning transmission electron microscopy and electron energy loss spectroscopy, together with in situ high energy resolution fluorescence detected X-ray absorption spectroscopy. The results revealed that a metallic Ni surface is crucial for effectively catalyzing the HOR, and that the formation of α-Ni(OH) 2 at potentials positive of +0.3 V vs. RHE leads to deactivation of the catalyst. Further analysis with theoretical calculations revealed a strong interaction between the Ni surface and graphene, resulting in a tightly sealed carbon shell that protects the Ni surface. The analysis further indicates that HOR occurs on graphene-protected Ni@C catalysts through the transport of hydrogen and protons across the carbon shell, particularly at self-healing larger holes. Using the Ni@C catalyst, together with evidence-informed experimental protocols to avoid oxidation before, during, and after membrane electrode assembly fabrication and testing, we achieved a milestone PGM-free AEMFC peak power density performance of 1.0 W/cm 2 . This is a demonstration of a Watt-scale performance for a PGM-free AEMFC.